1999
DOI: 10.7589/0090-3558-35.4.799
|View full text |Cite
|
Sign up to set email alerts
|

Serosurvey for Selected Disease Agents in White-tailed Deer from Mexico

Abstract: Serum samples from 350 white-tailed deer (Odocoileus virginianus texanus) collected in March 1994 from northeastern Mexico were tested for the prevalence of antibody activity against five infectious diseases of ruminants. The prevalence rate was 81% for bluetongue virus (BTV) of all serotypes, 72% for epizootic hemorrhagic disease virus (EHDV), 3% for Borrelia burgdorferi, 69% for Anaplasma marginale, and 0% for Brucella abortus, B. melitensis, and B. ovis. These are diseases that affect domestic ruminants, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
27
0
7

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 11 publications
3
27
0
7
Order By: Relevance
“…This may due to the use of the same range by cattle and deer and the persistent contamination of the grass and water sources used by both species. No antibodies to B. abortus were detected in our study; similar negative results have been reported for 37 white-tailed deer from Texas (Boeer, 1980), white-tailed deer from six ranches in the northeastern Mexico (Martinez et al, 1999), and from deer sampled in Minnesota (Ingebrigtsen et al, 1986). These negative results may in part relate to B. abortus control measures; at present, the prevalence of brucellosis in cattle in this area is ,0.5%.…”
supporting
confidence: 54%
See 1 more Smart Citation
“…This may due to the use of the same range by cattle and deer and the persistent contamination of the grass and water sources used by both species. No antibodies to B. abortus were detected in our study; similar negative results have been reported for 37 white-tailed deer from Texas (Boeer, 1980), white-tailed deer from six ranches in the northeastern Mexico (Martinez et al, 1999), and from deer sampled in Minnesota (Ingebrigtsen et al, 1986). These negative results may in part relate to B. abortus control measures; at present, the prevalence of brucellosis in cattle in this area is ,0.5%.…”
supporting
confidence: 54%
“…McCorquodale and DiGiacomo (1985) concluded that wild ungulates have little significance in transmitting brucellosis to cattle in the United States. In northeastern Mexico, 350 white-tailed deer were tested for the prevalence of antibodies against Brucella abortus and Brucella melitensis; no positive animals were detected, suggesting that deer in this area are not important in the epizootiology of brucellosis (Martinez et al, 1999). Surveys of wild ruminants in North America have found a wide range in antibody prevalence estimates for BVDV (Kahrs et al, 1964;Barrett and Chalmers, 1975;Kocan et al, 1986;Aguirre et al, 1995).…”
mentioning
confidence: 99%
“…This result is in accordance with the high seropositivity recorded in previous serological studies in this region (Suzan et al, 1983;Teclaw et al, 1985;Martinez et al, 1999). These observations suggest that eventually the population of domestic and wild ruminants could be affected with the infection of one or both viruses (Sailleau et al, 2012;Toye et al, 2013).…”
Section: Discussionsupporting
confidence: 81%
“…The detection and monitoring of these midges are important for the control of the pathogens that they can potentially transmit (Maclachlan and Mayo, 2013). In the northeastern region of Mexico, serological evidence has been reported in wild and domestic ruminants for both BTV and EHDV (Suzan et al, 1983), (Teclaw et al, 1985;Martinez et al, 1999). On the other side, BTV has been isolated from cattle and sheep in this and other regions of Mexico (Stott et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation